Electroconductive Rubber Composites Based on SBR Containing Carbon Black, Graphite, and Their Mixtures: Electrical Conductivity Changes During Cyclic Deformation - Hamed Peidayesh; Zdenko Špitalský; Ivan Chodák (Engineering Proceedings)
This contribution focuses on electroconductive elastomeric composites based on styrene–butadiene rubber filled with graphite, conductive carbon blacks, and a mixture of these fillers to investigate changes in their conductivity during cyclic deformation. Static conductivity, mechanical properties, and conductivity with simultaneous recording of the stress-strain curve were measured to characterize the composites. The composites containing higher amounts of graphite showed an increase in maximum stress and a decrease in conductivity dependency starting from the second cycle. The results show the potential to design and construct flexible conducting composites based on styrene–butadiene rubber in broad applications such as in the automotive industry.